(3OQQ GdfaGFS aj TCf GdcfGFSs - (3eMeO HOQ GdOjf Hf jMji GdbQGais ((3eMeO GdeOYh HTdHi GdHQGSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CYR GdESdGe hHYO abO LQJ MGOKI GdEYJfGA HbOQgG CeQ NWjQ hgj eSFdI GdcfGFS GdMGOKI HOejGW s
(3BNQgG (B:s
(3YOe LhGR GdEMOGK hefY GdQe ai GdbOje hgh GddGFb hdG CHbi efge OjGQkG cHGQkG hdG UZGQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3HBNQgG SDGd SFd Yfg GdTjN Rjf GdLjRi GdeGdcis
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B141s
Keywords: (3GdeLGejYs